Uptown [compact disc, unabridged] - Collier, Bryan (Live Oak Media, 2007)
Explore Harlem with its many sounds, colors and moods. Visit the Apollo Theater, play basketball at Ruckers Park, hear the Boy's Choir and see the sunset over the Harlem River.